2019
DOI: 10.1111/jcpe.13190
|View full text |Cite
|
Sign up to set email alerts
|

Activation of cannabinoid receptors promote periodontal cell adhesion and migration

Abstract: Objective Medical and recreational cannabis use is increasing significantly, but its impacts on oral health remain unclear. The aim of this study is to investigate the effects of tetrahydrocannabinol (THC), the major active component in cannabis, on periodontal fibroblast cell adhesion and migration to explore its role in periodontal regeneration and wound healing. Material and Methods The different distribution of cannabinoid receptors 1 (CB1) and 2 (CB2) was characterized in the mouse periodontium. Human per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 43 publications
3
17
0
3
Order By: Relevance
“…It was shown that AEA is able to control and restrict immune responses after primary CNS damage over a cannabinoid receptormediated pathway, and investigations further evidenced that AEA driven effects in microglia are mainly induced through CB2 receptors [23,42]. Recent works on PDL cells already found an impact of CB2 on cell adhesion and migration [9]. In the present study, CB receptor regulation in microglia was unaffected by stimulation, indicating a stable expression not being modulated by external influences.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…It was shown that AEA is able to control and restrict immune responses after primary CNS damage over a cannabinoid receptormediated pathway, and investigations further evidenced that AEA driven effects in microglia are mainly induced through CB2 receptors [23,42]. Recent works on PDL cells already found an impact of CB2 on cell adhesion and migration [9]. In the present study, CB receptor regulation in microglia was unaffected by stimulation, indicating a stable expression not being modulated by external influences.…”
Section: Discussionsupporting
confidence: 67%
“…Our previous investigations identified coexpression of cannabinoid receptors CB1 and CB2 on PDL cells, as it was seen for peripheral immune cells as well, potentially qualifying them as an important target for cannabinoid-driven regulation of periodontal immunology [8]. In addition, it was found that cannabinoids are able to promote periodontal cell adhesion and migration and thus induce cellular wound healing and regeneration processes [9]. Furthermore, CB receptor activation can facilitate osteogenic differentiation of PDL cells by upregulation of corresponding gene expression patterns and induction of mineralization processes, and presumably also in an inflammatory setting [10,11].…”
Section: Introductionmentioning
confidence: 82%
“…Both CB1 and CB2 receptors are found in periodontal tissues, and their expression may change under different conditions (Konermann, Jager, Held, Brossart, & Schmole, 2017;Liu, Qi, Alhabeil, Lu, & Zhou, 2019). In healthy periodontal tissues, CB1 receptors are expressed at a significantly higher level than CB2 receptors in periodontal ligament (PDL).…”
Section: Periodontal Tissuementioning
confidence: 99%
“…In periodontal tissues, several reports have suggested a role for both CB 1 and CB 2 receptors in pathological conditions, such as inflammation and wound healing [ 103 , 104 , 105 ]. Indeed, CB 1 are expressed at a significantly higher level than CB 2 receptors in both epithelium and periodontal ligaments (PDL) in periodontal tissues from healthy subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Periodontal tissue cannabinoid receptors have been suggested to differentially regulate cell growth and differentiation, inflammatory processes, and tissue healing [ 104 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 ], indicating that distinct expression patterns of CB 1 and CB 2 in PDL may be representative of distinct cellular function [ 104 , 106 , 107 , 108 , 109 ]. For instance, Liu et al showed that cannabinoids, by activating FAK and MAPK signaling in a CB 2 -dependent manner, trigger periodontal cell adhesion and migration [ 104 ], which provides evidence for therapeutic potential of cannabinoid compounds in periodontal regeneration and wound healing, possibly associated with the anti-inflammatory actions of CB 1 receptor activation, via NF-kappaB pathway inhibition in the periodontal tissue, as reported by Nakajima and colleagues [ 109 ].…”
Section: Introductionmentioning
confidence: 99%